The depositional settings of organic-rich shale in the faulted lacustrine basin: A case study of the Y1 Member of the Yingcheng Formation in the Songliao Basin - Haoxiang Lan; Min Guo; Meiyan Fu; Jon Gluyas; Hengwei Guo; Danlong Li; Can Ling; Guanghui Duan; Fengcun Xing (Oil Shale, 2024)
Volcanic activity is often associated with the development of faulted lacustrine basins. Organic-rich shale in such basins usually contains abundant volcanic material. The influence of volcanic input on organic-rich shale deposition in the basin studied has not been discussed in detail. Based on the ten shale samples from three wells, this study analyzed the depositional environment of the Yingcheng Formation shale in the Lishu Fault Depression area of the Songliao Basin by using interpretation of logging, total organic carbon analysis, gas chromatography mass spectrometry analysis, and trace element analysis. The impact of fault break to basement and volcanic materials on the organic matter enrichment was evaluated. The results show that the organic matter of Ying 1 (Y1), the First Member of the Yingcheng Formation, in the Lishu Fault Depression is characterized mainly by type I kerogen. The shale of the Y1 Member, having high total organic carbon content, is laterally continuous and could be considered as a potential target for shale oil exploration. The shale with high total organic carbon was deposited in a freshwater deep lake under an anoxic environment. There is a significant input of volcanic material, especially around the Su2 well near the Sangshutai Fault. This study has established a sedimentary model of organic-rich shale in the faulted lacustrine basin affected by volcanic activity, which has significance for the exploration of shale oil in faulted lacustrine basins.